Language Intelligence Development of English Multimedia Teaching considering Collaborative Filtering Topic Search Algorithm - Xiaodong Zhu; Fen Huang (Advances in Multimedia)
With the opening up of our country, English has become one of the necessary skills for foreign communication. Traditional English teaching can no longer meet the needs of learning. It is necessary to introduce computer, multimedia, and other technologies to supplement students to improve students’ autonomous learning ability and learning interest. This is extremely important for the evaluation of English multimedia teaching. Based on the collaborative filtering topic search algorithm, this article tries to sort out the influence of English synthesis and English specialization on the development of language intelligence for English multimedia teaching and analyzes and promotes the improvement of students’ interest in learning English and the improvement of classroom self-learning awareness. The results of simulation experiments show that the collaborative filtering topic search algorithm is effective and can support the development of language intelligence in English multimedia teaching.